2020
DOI: 10.1093/cercor/bhaa116
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Effects of Dopamine D1 Receptor Activation on Visuomotor Coordination Task Performance

Abstract: Dopamine plays an important role in the modulation of neuroplasticity, which serves as the physiological basis of cognition. The physiological effects of dopamine depend on receptor subtypes, and the D1 receptor is critically involved in learning and memory formation. Evidence from both animal and human studies shows a dose-dependent impact of D1 activity on performance. However, the direct association between physiology and behavior in humans remains unclear. In this study, four groups of healthy participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…For example, dopamine neuron activity is known to scale with the magnitude of an anticipated reward (49,50). The inverted-U relationship present in the animals' success rates resembles those seen in studies relating the activity of neuromodulators such as dopamine and norepinephrine to performance in working memory, visuomotor, and attention tasks (37,38,51,52). These studies demonstrate that a graded release of a neurotransmitter can lead to discontinuities in behavioral performance.…”
Section: Relationships To Theories Of the Neural Basis Of Choking Undermentioning
confidence: 65%
“…For example, dopamine neuron activity is known to scale with the magnitude of an anticipated reward (49,50). The inverted-U relationship present in the animals' success rates resembles those seen in studies relating the activity of neuromodulators such as dopamine and norepinephrine to performance in working memory, visuomotor, and attention tasks (37,38,51,52). These studies demonstrate that a graded release of a neurotransmitter can lead to discontinuities in behavioral performance.…”
Section: Relationships To Theories Of the Neural Basis Of Choking Undermentioning
confidence: 65%
“…Populations of dopaminergic neurons in the midbrain are implicated in reward processing by encoding incentive salience of the stimuli (Berridge and Kringelbach, 2015) and reward prediction error (Schultz, 2016). The research in animal models and humans supports the involvement of the dopaminergic system in cognitive functions such as sustained attention (Bellgrove et al, 2005), working memory (Bäckman and Lyberg, 2013), executive control (Saloner et al, 2020), as well as visuomotor search (Chen et al, 2020). Several resting-state studies have found the functional connectivity of VTA and SNc to be related to aspects of reward processing (Adrián-Ventura et al, 2019; Schmaal et al, 2012), impulsivity (Grimm et al, 2020), interoception (Chong et al, 2017) and gait speed (Karim et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…The visual motor processing task has been used in several animal and human studies [83][84][85] with related to premotor cortex activation of motor movement and co-activated with middle temporal and superior temporal regions by human tCDS 83 and fMRI 84 exam. The basic psychometric properties of the task in human were considered adequate.…”
Section: Visual Motor Processing Taskmentioning
confidence: 99%
“…The basic psychometric properties of the task in human were considered adequate. 84 The participant is instructed to use the joystick provided to track the round dots randomly showed on the screen and the task was divided into three blocks (12 min each) with 41 trials each, and the initial correct score and the learning curve were both evaluated. Before the formal tasks, we demonstrated the task at first and made all the participants to practice to follow the target dot with the joystick five times to ensure they understand the task instruction.…”
Section: Visual Motor Processing Taskmentioning
confidence: 99%